Recent Advances in Neural Circuits for Taste Perception in Hunger - Fu, Ou; Minokoshi, Yasuhiko; Nakajima, Ken-ichiro (Frontiers in Neural Circuits, 2021)
Feeding is essential for survival and taste greatly influences our feeding behaviors. Palatable tastes such as sweet or umami trigger feeding as a symbol of a calorie-rich diet containing sugar or proteins, while unpalatable tastes such as bitter or sour terminate further consumption as a warning against ingestion of harmful substances. Therefore, taste is considered a criterion to distinguish whether food is edible. However, perception of taste is also modulated by physiological changes associated with internal states such as hunger or satiety. Empirically, during hunger state, humans find ordinary food more attractive and feel less aversion to food they usually dislike. Although functional magnetic resonance imaging studies performed in primates and in humans have indicated that some brain areas show state-dependent response to tastes, the mechanisms of how the brain senses tastes during different internal states are poorly understood. Recently, using newly developed molecular and genetic tools as well as in vivo imaging, researchers have identified many specific neuronal populations or neural circuits regulating feeding behaviors and taste perception process in the central nervous system. These studies could help us understand the interplay between homeostatic regulation of energy and taste perception to guide proper feeding behaviors.